2020
DOI: 10.1016/j.psj.2019.11.036
|View full text |Cite
|
Sign up to set email alerts
|

Research Note: Detection of infectious bursal disease virus antibodies in free-living wild birds in Zaria, Nigeria

Abstract: Infectious bursal disease virus ( IBDV ) is an immunosuppressive pathogen of poultry causing great economic losses to the poultry industry. In this study, the IBDV antibodies were detected in captured free-living wild birds in Zaria, Nigeria. One hundred and fifty free-living wild birds, comprising 30 birds each of 5 different species, were sampled over a period of 9 months. Blood samples were collected from each bird, and harvested sera were tested for IBDV antibodies using enzyme-linke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Indeed, recent studies have shown that when IBDV strains of two genotypes co-infect the same cell, their respective viral replication factories co-accumulate, thereby providing an opportunity for segment reassortment among the different genotypes ( 40 ). Recent studies have shown that wild birds can act as carriers of IBDV to transmit the virus to chickens ( 41 , 42 ), which might increase the risk of chickens infecting multiple genotypes of IBDV.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recent studies have shown that when IBDV strains of two genotypes co-infect the same cell, their respective viral replication factories co-accumulate, thereby providing an opportunity for segment reassortment among the different genotypes ( 40 ). Recent studies have shown that wild birds can act as carriers of IBDV to transmit the virus to chickens ( 41 , 42 ), which might increase the risk of chickens infecting multiple genotypes of IBDV.…”
Section: Discussionmentioning
confidence: 99%
“…They are both sedentary and migratory [20], and migration is from cooler areas to warmer areas triggered by rainfall [19]. Due to their migratory potentials, cattle egrets have been implicated in the spread of poultry infections such as infectious bursal disease [3,23], Newcastle disease [24] and chicken infectious anaemia [4].…”
Section: Cattle Egretmentioning
confidence: 99%
“…The mode of infection of these birds could only be speculated from their migration to locations where the infectious agents are present. Some of these infectious agents could cause clinical signs in other domestic animals but not in the free-living wild birds [1]; Fagbohun et al [2][3][4]. The significant roles that these wild birds play in the epidemiology of diseases would only be better understood from using them in experimental studies, thus requiring putting them in captivity.…”
Section: Introductionmentioning
confidence: 99%
“…Chickens, among other domestic poultry, are natural hosts for IBD. The fecal-oral route is the most common route of transmission of the IBDV, after that the aerosol method [4]. IBD can affect both commercial and backyard chickens in an equal way [5].…”
Section: Introductionmentioning
confidence: 99%